Versatile bimetallic lanthanide metal-organic frameworks for tunable emission and efficient fluorescence sensing - Su, Yan (2019)
Developing novel lanthanide metal-organic frameworks (Ln-MOFs) to rapidly and reliably differentiate both metal ions in solution and volatile organic compounds (VOCs) in vapor is highly challenging. Here, we describe versatile Eu3+/Tb3+-MOFs based on a flexible ligand. It is noteworthy that the film fabricated using bimetallic Eu0.47Tb0.63-MOF and polyvinyl alcohol could serve as an easy and convenient luminescent platform for distinguishing different metal ions and VOCs. The luminescent film exhibits notable fingerprint correlation between the metal ions/VOCs and the emission intensity ratio of Eu3+/Tb3+ ions in Ln-MOFs. As a result, the bimetallic Ln-MOFs show fast recognition of Fe3+ ion with a response time of <10 s, and can effectively probe styrene vapor within 4 min. Since the developed Ln-MOF film is stable and reliable, this work presents a promising strategy to explore luminescent platforms capable of effectively sensing different metal ions and VOCs.